Design and construction of a compact low-cost test bench for hybrid engine studies - Trejo Mandujano, Hector Alejandro (2022)
In this paper, the design, construction and first results of a low-cost hybrid engine test bench is presented. The purpose of this device is to allow geographically specific research around control algorithms and architectures for hybrid engines. The system consists of an internal combustion engine parallel-coupled to a direct current electrical motor, which can independently supply power to an inertial load. The device includes a management circuit that uses sensors, actuators, displays and memory devices around a micro-controller to control power delivery, acquire information, display, and save data needed for the investigation. The general objective of this low-cost device is to make several tests under different conditions to infer the cost/benefit of converting an original internal combustion powered vehicle into a hybrid, considering the city specific transportation needs. As result, the mechanical and electronic design are shown in the data acquisition as well of the first experimental tests as proof of concept